Bespoke versus off-the-shelf ankle-foot orthosis for people with stroke: randomized controlled trial. (March 2018) - Tyson, Sarah F; Vail, Andy; Thomas, Nessa; Woodward-Nutt, Kate; Plant, Sarah; Tyrrell, Pippa J
Objective: The aim of the study was to compare the effect of two designs of ankle-foot orthosis on people with stroke. Design: The study design was an assessor-blind, multicentre randomized controlled trial. Setting: The setting was community stroke services. Participants: A total of 139 community-dwelling stroke survivors with limited mobility were recruited. Interventions: The two most commonly used types of ankle-foot orthosis (bespoke and off-the-shelf) were chosen. Main measures: The main measures of the study were as follows: short- (6 weeks) and long-term (12 weeks) effects on stroke survivors' satisfaction; adverse events; mobility (Walking Handicap Scale); fear of falling (Falls Efficacy Scale–International (FES-I)) and walking impairments (gait speed and step length using the 5-m walk test). Results: Long-term satisfaction was non-significantly higher in the off-the-shelf group: 72% versus 64%; OR (95% CI) = 0.64 (0.31 to 1.3); P  = 0.21. No statistically significant differences were found between the orthoses except that the off-the-shelf group had less fear of falling at short-term follow-up than the bespoke group: mean difference (95% CI) = −4.6 (−7.6 to −1.6) points on the FES-I; P  = 0.003. Conclusion: No differences between off-the-shelf and bespoke ankle-foot orthoses were found except that participants in the off-the-shelf orthosis group had less fear of falling at short-term follow-up.